Daniel Arbuckle's Mastering Python : building powerful Python applications - Arbuckle, Daniel (Packt Publishing, 2017)
Gain a thorough understanding of operating in a Python development environment, and some of the most important advanced topics with Daniel Arbuckle. This dynamic, concise book is full of real-world solutions for Python 3.6 problems, and advanced-level concepts such as reactive programming, microservices, ctypes and Cython. About This Book Covers the latest and advanced concepts of Python such as parallel processing with Python 3.6 Explore the Python language from its basic installation and setup to concepts such as reactive programming and microservices Get introduced to the mechanism for rewriting code in a compiled language along with ctypes and Cython tools Who This Book Is For If you are a programmer and are familiar with the basics of Python, and you want to broaden your knowledge base to develop projects better and faster, this book is for you. Even if you are not familiar with Python, Daniel Arbuckle's Mastering Python starts with the basics and takes you on a journey to become an expert in the technology. What You Will Learn Get to grips with the basics of operating in a Python development environment Build Python packages to efficiently create reusable code Become proficient at creating tools and utility programs in Python Use the Git version control system to protect your development environment from unwanted changes Harness the power of Python to automate other software Distribute computational tasks across multiple processors Handle high I/O loads with asynchronous I/O to get a smoother performance Take advantage of Python's metaprogramming and programmable syntax features Get acquainted with the concepts behind reactive programming and RxPy In Detail Daniel Arbuckle's Mastering Python covers the basics of operating in a Python development environment, before moving on to more advanced topics. Daniel presents you with real-world solutions to Python 3.6 and advanced-level concepts, such as reactive programming, microservices, ctypes, and Cython tools. You don't need to be familiar with the Python language to use this book, as Daniel starts with a Python primer. Throughout, Daniel highlights the major aspects of managing your Python development environment, shows you how to handle parallel computation, and helps you to master asynchronous I/O with Python 3.6 to improve performance. Finally, Daniel will teach you the secrets of metaprogramming and unit testing in Python, helping you acquire the perfect skillset to be a Python expert. ...